Natural frequencies of FG plates with two new distribution of porosity - Merdaci, Slimane; Hadj Mostefa, Adda; Khayal, Osama M.E.S. (Zielona Góra: Uniwersytet Zielonogórski)
The functionally graded plates (FGP) with two new porosity distributions are examined in this paper. In this work the plate is modeled using the higher-order shear deformation plate principle. The shear correction variables are neglected. To evaluate the equations of motion, the Hamilton method will be used herein. Therefore, the free vibration analysis of FG plate is developed in this work.
Keywords: functionally graded plates; natural frequency; even; uneven; porosity